LabVIEW Based a Software System: Quantitative Determination of Main Electronic Parameters for Schottky Junction Structures - ÇİÇEK, Osman; KURNAZ, Sedat (Balkan Journal of Electrical & Computer Engineering (BAJECE), 2019)
LabVIEW is a software development platform that can be programmed with a graphical interface and so, measurement and instrumentation problems are used to deliver a solution. In the sensor applications, it is very important to calculate the main electronic parameters of the produced samples and it takes a lot of time to calculate these parameters and evaluate results. Therefore, LabVIEW based a software system was developed to minimize the time spent. In this way, it was used to make the analysis as fast as possible. This study aimed to calculate quickly the obtained results from the measurement system. For this purpose, AuPd/n-GaAs Schottky Junction Structure (SJS) was produced by using RF and DC sputtering techniques to investigate on electronic parameters of SJS. The forward and reverse current-voltage (I-V) of SJS at ±3V were measured at room temperature (295 K). By using thermionic emission (TE) theory, Ohm’s law, Cheung and Cheung’s function and modified Norde’s function, the electronics parameters such as the series resistance (Rs), the shunt resistance (Rsh), the barrier height (ΦB0) and the ideality factor (n) were calculated and graphics, which were drawn according to these models, via the developed software platform.
Keywords: LabVIEW; a software system; Electronic Parameters; Schottky Junction Structures; Elektrik Mühendisliği; Electrical Engineering